Gender Differences in the Co-Use of Tranquilizers, Sedatives, Sleeping Pills and Alcohol among Spanish Adolescents: A Nationwide Population-Based Study - Pilar Carrasco-Garrido; Isabel Jiménez-Trujillo; Valentín Hernández-Barrera; Lidiane Lima Florencio; Spencer Yeamans; Domingo Palacios-Ceña (MDPI AG, 2024)
Adolescence is a critical developmental stage for the initiation of substance use worldwide, which is one of the main risk-taking behaviors that may impact adolescents' physical and mental well-being. The aims of this study were to (1) assess the prevalence of the co-use of tranquilizers, sedatives, and sleeping pills with alcohol (TSSp&AC) by gender in the Spanish adolescent population in 2018 and (2) identify the variables associated with TSSp&AC. An observational cross-sectional study following STROBE guidelines was conducted. We analyzed data from 38,010 adolescents aged 14 to 18 years old (18,579 males and 19,431 females) who participated in ESTUDES (Survey on Drug Use in Secondary Education in Spain) 2018. Female adolescents reported a higher prevalence of TSSp&AC than males (p < 0.001). The factors associated with female co-use were being 16-18 years of age (OR 1.65); the consumption of tobacco (OR 1.73), cocaine (OR 1.84), other illicit psychoactive drugs (OR 1.89); and novel illicit psychoactive drugs (OR 1.74); no perceived health risk from the consumption of TSSps (OR 2.45); and the perceived availability of TSSps (OR 2.23) and alcohol (OR 2.09). There are several factors associated with TSSp&AC in Spanish female adolescents with potential implications for healthcare providers.